A Light Field Display Realization with a Nematic Liquid Crystal Microlens Array and a Polymer Dispersed Liquid Crystal Film - Hui Li; Yancheng He; Yi Yu; Yuntao Wu; Shuiping Zhang; Yanduo Zhang (Photonics, 2022)
This study demonstrates a light field display system using a nematic liquid crystal (LC) microlens array (MLA) and a polymer dispersed liquid crystal (PDLC) film. LC-MLA without polarization effects presented high-resolution intermediate 3D images by adopting a depolarization algorithm. The adopted PDLC film modulated the reconstructed 3D images to deliver full-parallax images efficiently with a wide FOV. The experimental result shows that the peak signal to noise ratio (PSNR) value of photograph accurate display results improves compared to the pure LC-MLA method. The proposed method is an essential step toward high-quality light field display.